1990
DOI: 10.1254/jjp.53.331
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Wound Healing by Royal Jelly (RJ) in Streptozotocin-Diabetic Rats

Abstract: Abstract-Chronically diabetic rats prepared by a single i.v. Injection of strepto zotocin were used to study whether royal jelly (RJ) possesses a hypoglycemic reaction and whether it can augment wound healing. Oral RJ administration of 10, 100 and 1000 mg/kg/day did not show any insulin-like activity (the hypo glycemic reaction). RJ, however, showed some anti-inflammatory activity by decreasing exudation and collagen formation in granulation tissue formation in the cotton pellet method. RJ also shortened the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
72
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 11 publications
1
72
0
1
Order By: Relevance
“…Commercial RJ is obtained by harvesting the brood food from the queen cell in the 3rd day of larval development (ISO 12824:2016). (Fujii et al, 1990;Kohno et al, 2004), immunoregulatory (Okamoto et al, 2003;Vucevic et al, 2007), insulin-like (Dixit and Patel, 1964;Kramer et al, 1982), estrogen signaling mediating (Moutsatsou et al, 2010), antiaging (Inoue et al, 2003), reducing cholesterol levels (Kashima et al, 2014), vasodilation (Tokunaga et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Commercial RJ is obtained by harvesting the brood food from the queen cell in the 3rd day of larval development (ISO 12824:2016). (Fujii et al, 1990;Kohno et al, 2004), immunoregulatory (Okamoto et al, 2003;Vucevic et al, 2007), insulin-like (Dixit and Patel, 1964;Kramer et al, 1982), estrogen signaling mediating (Moutsatsou et al, 2010), antiaging (Inoue et al, 2003), reducing cholesterol levels (Kashima et al, 2014), vasodilation (Tokunaga et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated a wide range of health benefits to humans and model organisms, including vasodilative and hypotensive activities (Tokunaga et al, 2004), antitumor (Tamura et al, 1987), anti-inflammatory (Fujii et al, 1990;Kohno et al, 2004), antibacterial and disinfectant properties (Fujiwara et al, 1990;Shen et al, 2010a), antifatigue activity (Kamakura et al, 2001a), and increasing the average lifespan in mice (Inoue et al, 2003) and nematodes (Honda et al, 2011). Because of its great potential benefits to human health, RJ is widely used as a key component in many commercial products including medicine, dietary supplements, and cosmetics (Kamakura et al, 2001c).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, RJ exhibits immunomodulatory properties (3,22,24) and inhibits the development of atoptic dermatitis-like skin lesions (26). Earlier we found that RJ had the ability to induce neurites from cultured rat pheochromocytoma PC12 cells (10), which prompted us to test the effects of RJ and its components on NSCs cultured from the central nervous system (CNS).…”
mentioning
confidence: 99%